2007 IEEE International Geoscience and Remote Sensing Symposium 2007
DOI: 10.1109/igarss.2007.4423761
|View full text |Cite
|
Sign up to set email alerts
|

Digital metric camera radiometric and colorimetric calibration with simultaneous CASI imagery to a CIE standard observer based colour space

Abstract: The Institut Cartogràfic de Catalunya (ICC) operates a Digital Metric Camera (DMC), manufactured by Z/Imaging. It supports the simultaneous capture of panchromatic, RGB colour and near-infrared images. One of the most important ICC products is the Catalonia orthophotomap series. This product is intended to depict the territory as realistically as possible. With this aim, ICC is developing a project to obtain genuine colours in the photographic products produced with the DMC camera and this paper contains some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…Relative radiometric calibration normalizes the output of the sensor so that an uniform response is obtained in the entire image area when the focal plane of the sensor is irradiated with a uniform radiance field; for a single band, the corrections are determined at least for sensitivity differences of individual cells of a CCD array, defect pixels, light falloff, and dark signal [36,37]. Spectral response calibration determines the system's response as a function of wavelength for each channel [33,35] and colorimetric calibration determines the relationship between the sensor and standard color spaces [38]. PSF-calibration determines the system's response to a point source [1].…”
Section: Radiometric Calibrationmentioning
confidence: 99%
See 3 more Smart Citations
“…Relative radiometric calibration normalizes the output of the sensor so that an uniform response is obtained in the entire image area when the focal plane of the sensor is irradiated with a uniform radiance field; for a single band, the corrections are determined at least for sensitivity differences of individual cells of a CCD array, defect pixels, light falloff, and dark signal [36,37]. Spectral response calibration determines the system's response as a function of wavelength for each channel [33,35] and colorimetric calibration determines the relationship between the sensor and standard color spaces [38]. PSF-calibration determines the system's response to a point source [1].…”
Section: Radiometric Calibrationmentioning
confidence: 99%
“…In Finland, comprehensive campaigns with various systems have been carried out at the Sjökulla test field [1,2,13,50]. Institut Cartogràphic Catalonia (ICC) has performed comprehensive campaigns with DMC at the Banyoles test field [38,51,52]. The German Society for Photogrammetry and Remote Sensing (DGPF) carried out test flights with many systems at the Vaihingen/Enz test field in Germany in the summer of 2008 [53].…”
Section: Radiometric Calibrationmentioning
confidence: 99%
See 2 more Smart Citations
“…The empirical investigations of radiometric properties of the large-format digital photogrammetric sensors have shown that they have high radiometric performance potential, including linearity, large dynamic range, great radiometric resolution and they are suited for radiometric calibration (Honkavaara and Markelin, 2007;Markelin et al, 2008;Martínez et al, 2007; Arbiol, 2008). However, many questions still concern the entire processing chain of photogrammetric images (Honkavaara et al, 2009).…”
Section: Introductionmentioning
confidence: 99%